1995
DOI: 10.1002/jsfa.2740670402
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive quality evaluation of fresh prunes by NMR spectroscopy

Abstract: The potential for utilizing nuclear magnetic resonance measurements for evaluating the quality of fresh prunes was investigated. In a 2 T magnetic flux density, the chemical shift between proton hydrogens of soluble solids and those of water is less than 100 Hz. The band width of the water resonance spectrum of fruits is relatively large and therefore it is dificult to resolve between the spectral peaks of water and soluble solids. Measurements with a 100 mm Birdcage coil failed to resolve between the resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Interference from localised Ðeld gradients in two-dimensional data collection is avoided by analysing the spectral characteristics of the whole fruit. Use of surface coils to generate homogeneous magnetic Ðelds in particular regions of the sample and analysing the sugar/water ratio of their respective spectral peaks (Zion et al 1995), or using the strong relationship between self-di †usion and sucrose concentration in aqueous solution (Wai et al 1995), are the more successful approaches currently being evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interference from localised Ðeld gradients in two-dimensional data collection is avoided by analysing the spectral characteristics of the whole fruit. Use of surface coils to generate homogeneous magnetic Ðelds in particular regions of the sample and analysing the sugar/water ratio of their respective spectral peaks (Zion et al 1995), or using the strong relationship between self-di †usion and sucrose concentration in aqueous solution (Wai et al 1995), are the more successful approaches currently being evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there has been no concerted attempt to link changes in MR parameters obtained from quantitative images to variation in other physicochemical properties, like carbohydrate composition, which would be expected to a †ect the magnetic characteristics of cell solutions. Di †erence in soluble solids content (SSC), for example, is currently being explored as the basis for an MR sensor to assess sweetness of fruit (Zion et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Clark & Burmeister (1999) utilizaram a MRI para identificar injúrias em maçãs, causadas por altas concentrações de CO2 durante o armazenamento sob condições de atmosfera controlada. Vários autores vêm utilizando a tomografia de ressonância magnética, como método não destrutivo, a fim de avaliar a qualidade de frutas frescas (Zion, et al, 1995;Hall et al, 1998;Biscegli et al, 2000;Gonzales et al, 2001). Chen et al (1996) e Clark et al (1999 utilizaram a MRI para acompanhar o desenvolvimento em frutas, através de medidas quantitativas fornecidas pelas imagens.…”
Section: Introductionunclassified
“…1999. unique parameters relating to mobile water fractions determined in NMR experiments, ought to be sensitive to changes in solution properties such as viscosity and composition (Bloembergen et al, 1948;Carver and Richards, 1972). Indeed, NMR analysis is the basis of one approach for nondestructive testing for soluble solids (Zion et al, 1995). And secondly, investigations of ripening fruit (Goodman et al, 1996;Ishida et al, 1994) and soybean nodules (MacFall et al, 1992) have shown that relaxation properties change with time, and with imposition of experimental treatments affecting specific biochemical reactions.…”
mentioning
confidence: 99%